Imaginative Culture and the Enriched Nature of Positive Experience - Barrett, Nathaniel F. (Frontiers in Psychology, 2022)
To understand the evolution of imaginative culture, we need to understand its unique affective power. The purpose of this article is to explain our enjoyment of imaginative culture from the standpoint of a distinctive theoretical approach to understanding affect in terms of the dynamic and energetic features of consciousness. This approach builds upon John Dewey’s view of enjoyment as the enrichment of experience, adding perspectives from studies of the dynamics of consciousness and from ecological psychology. Its main thesis is that positive affect is determined by the causal enrichment of experience, which is defined as the differentiated-ness of conscious states. This approach suggests that the affective power of imaginative culture lies in the way it affords experiences of enriched meaning, as exemplified by our enjoyment of highly nuanced emotion in music.